Geometric morphometric evaluation of cervical vertebrae shape and its relationship to skeletal maturation. - Chatzigianni, Athina; Halazonetis, Demetrios J (Am J Orthod Dentofacial Orthop, 2009)
INTRODUCTION: Cervical vertebrae shape has been proposed as a diagnostic factor for assessing skeletal maturation in orthodontic patients. However, evaluation of vertebral shape is mainly based on qualitative criteria. Comprehensive quantitative measurements of shape and assessments of its predictive power have not been reported. Our aims were to measure vertebral shape by using the tools of geometric morphometrics and to evaluate the correlation and predictive power of vertebral shape on skeletal maturation. METHODS: Pretreatment lateral cephalograms and corresponding hand-wrist radiographs of 98 patients (40 boys, 58 girls; ages, 8.1-17.7 years) were used. Skeletal age was estimated from the hand-wrist radiographs. The first 4 vertebrae were traced, and 187 landmarks (34 fixed and 153 sliding semilandmarks) were used. Sliding semilandmarks were adjusted to minimize bending energy against the average of the sample. Principal components analysis in shape and form spaces was used for evaluating shape patterns. Shape measures, alone and combined with centroid size and age, were assessed as predictors of skeletal maturation. RESULTS: Shape alone could not predict skeletal maturation better than chronologic age. The best prediction was achieved with the combination of form space principal components and age, giving 90% prediction intervals of approximately 200 maturation units in the girls and 300 units in the boys. Similar predictive power could be obtained by using centroid size and age. Vertebrae C2, C3, and C4 gave similar results when examined individually or combined. C1 showed lower correlations, signifying lower integration with hand-wrist maturation. CONCLUSIONS: Vertebral shape is strongly correlated to skeletal age but does not offer better predictive value than chronologic age.
Keywords: Adolescent; Age Determination by Skeleton; Age Factors; Anthropometry; Body Weights and Measures; Bone Development; Cephalometry; Cervical Vertebrae; Child; Female; Hand; Humans; Image Processing, Computer-Assisted; Male; Odontoid Process; Predictive Value of Tests; Sex Characteristics; Wrist